Facilities improvement for sustainability of existing public office buildings in Nigeria - Kasim, Rozilah; Martin, David; Adeyemi, Adegbenga; Adeyemi, Ifeoluwa Adedoyin (African Journal Online (AJOL), 2017)
The study examined the building design features of a cosmopolitan public office building in Abuja. The features were classified into Spatial Plan, Structure and Facilities, to determine which of the 3 variables requires urgent sustainable improvement from end-users' perspective in existing public office buildings in developing countries. A quantitative approach was adopted while the research strategy involved survey and direct observation. Post-Occupancy Evaluation was used to collect the survey data on a massive public office building in Nigeria, which reflected the quota system and federal character of the nation, as study area. A total of 339 useable questionnaires were retrieved from the respondents, and the analysis conducted revealed that facilities requires the most urgent improvement for sustainability. It was therefore recommended that facilities should be given priority for successful sustainable improvement of public office buildings above other design features.